Efforts to Develop Coban Glotak Waterfall Tourism in Dalisodo Village, Wagir District, Malang Regency, Indonesia - Riawati, Enik; Ruja, I Nyoman; Adi, Khofifatu Rohmah (Humanities Horizon, 2024)
Tourism Development has become a trend That continues to grow in recent years. Various developments are dynamically adapted to meet tourist needs. The purpose of this research is to describe the Development of tourism potential to attract visitors, development strategies and obstacles in the Coban Glotak Waterfall Tourism. This type of Research is descriptive research with a qualitative approach. The research was conducted in Dalisodo Village, Wagir District, Malang Regency. The data collection method Led in this research consists of conservation, interview, and documentation and for data analysis using an interactive analysis model. This research found that the tourism potential that can be developed in the Coban Glotak Waterfall Tourism is that Coban Glotak has a waterfall height of approximately 70 meters and there is a "stacked rock" site. Strategies that can be developed are promoting through social media. Meanwhile, the obstacles to this tourism are the many damaged facilities and the lack of concern of the surrounding community about this tourism. The implication of the results of this research can be used by Coban Glotak waterfall tourism managers and the forestry government to fund the management of Coban Glotak waterfall Tourism.